Strengthening National Identity in the Era of Globalization Through Digital Literacy at SMAN 5 Mataram - Baiq Fina Maulidiya; Dewinta Fitri Cahyani (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to explore how digital literacy can be used to strengthen the understanding and awareness of national identity among students at SMAN 5 Mataram. The research Use a qualitative approach with a phenomenological method, using data collection techniques such as interviews, observations, and documentation. The research subjects are teachers and students at SMAN 5 Mataram.The research findings show that the strengthening of national identity through digital literacy at this school consists of several aspects, That is: (1) the level of students' digital literacy in facing the influence of globalization, (2) the role of digital literacy in strengthening national identity among students, (3) digital literacy can be used to strengthen the understanding and awareness of national identity among students, and (4) the challenges of digital literacy in the era of globalization in strengthening national identity.